Virtual consultation in lupus during the COVID-19 pandemic – patients' perspective - Keerthi Talari (Indian Journal of Rheumatology)
Background: Virtual consultations have become the norm during the COVID-19 pandemic with disruption of regular outpatient services due to fear of infection and travel restrictions. Methodology: A telephonic survey was conducted among 54 patients with systemic lupus erythematosus (SLE) who sought virtual consultations to understand patients' perspective about these consultations. Results: 42/54 (77.78%) patients had inactive disease. Most patients (42/48 [87.5%]) did not visit the hospital for fear of COVID, whereas 58% of them also had travel restrictions. About one-fourth of individuals felt that consultation from home was comfortable (12/48 [25%]), cost-saving (14/48 [29.16%]) and they preferred virtual over physical consultation (14/48 [29.16%]). The satisfaction levels of patients during the process of booking appointment, the consultation process, and postconsultation queries also seem adequate. Conclusion: Virtual consultations in SLE are a feasible and conceivable option, especially for those with inactive disease on stable treatment.